Analisis Kelayakan Panjang Dermaga Curah Cair Berdasarkan Data Kunjungan Kapal Di Pelabuhan Dumai - Manik, Bramson P; Trimaijon, Trimaijon; Fatnanta, Ferry (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The length’s advisability of the berth can be seen from the Berth Occupancy Ratio (BOR). The pour liquid berth (Berth B) in Dumai’s harbor is one of the berth which has a higher activity and the ships that come increasing everyday. The increasing ships in Berth B need a project to know the value of visiting ships and the value of BOR in short term, middle term and long term. Project is done in order Berth B can hold the ships that will tether by adding the length of berth.The value of BOR in short time projection until 2019 is 75,86 % and the number of ships are 744. To fulfill The Standard Of Managing Director Of Marine in 2011, the value of BOR was 69% therefore the berth should be lengthened about 70 meters. In 2019 the short time projection the length of Berth B becomes 870 meters.Based on project result the visiting ships are 984, the value of BOR in middle term is 87,94% in 2024. To fulfill the value of BOR which is 69%, the Berth should be lengthnened formerly 870 meters become 1100 meters.The long term projection until 2029 the value of BOR is 83,71% with the number of visiting ships 1224. To fulfill the value of BOR that is 69%, the Berth should be lengthnened around 220 meters. The length of berth totally 1320 meters which is formerly 1100 meters in 2029Keywords: harbour, berth, visiting ships, BOR, projection